The Influence of Product Quality and Sales Promotion on Repurchase Intention & Impulsive Buying (Marketing Management Literature Review) - Erik Junikon; Hapzi Ali (Dinasti International Journal of Management Science, 2022)
The literature review article on the influence of product quality and sales promotion on repurchase intention and impulsive buying is a scientific article that aims to build hypothesis research on the impact of variables to be used in further study within the scope of marketing management science. The library research method has been used to write this literature review article and used sources from online resources such as Google Scholar, Mendeley, and other academic online resources. The result of this literature review article are: 1) product quality affects repurchase intention; 2) sales promotions affect repurchase intention; 3) product quality affect impulsive buying; 4) sales promotions affect impulsive buying; and 5) repurchase intention affects impulsive buying. Besides the 2 (two) exogenous variables that influence the endogenous variables of repurchase intention and impulsive buying, there are still many other factors, including consumer satisfaction, product advertising, and brand ambassadors.